Use of Monte Carlo simulation and considerations for PK-PD targets to support antibacterial dose selection. (October 2017) - Trang, Michael; Dudley, Michael N; Bhavnani, Sujata M
Highlights: Use of Monte Carlo simulation to support antibacterial dose selection. Inputs for PK-PD target attainment analyses to support antibacterial dose selection. Discussion of clinical PK-PD analyses for efficacy and safety to support dose selection. Abstract : Monte Carlo simulation is used to generate data for pharmacokinetic–pharmacodynamic (PK-PD) target attainment analyses to assess antibacterial dosing regimens in early and late stage drug development. Careful consideration of the quality of data for pharmacokinetics, non-clinical PK-PD targets for efficacy, the choice of the bacterial reduction endpoint upon which the PK-PD target is based, variability in the PK-PD target, and effect site exposures ensures optimal dose selection. Relationships between drug exposure and efficacy and/or safety endpoints based on clinical data can also be applied to simulated data to support dose selection. These in silico analyses, conducted throughout drug development, provide the greatest opportunity to de-risk the development of antibacterial agents.